2020
DOI: 10.1111/tbed.13777
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variant of Burkholderia mallei detected in Kuwait: Consequences for the PCR diagnosis of glanders

Abstract: Glanders is a contagious zoonotic disease caused by Burkholderia mallei. Following the detection of glanders positive horses using the OIE complement fixation test, the tissues of two horses were analysed by PCR. While PCR systems targeting the Burkholderia pseudomallei complex gave positive signals, the species-specific PCR systems targeting B. mallei (fliP-IS407A) and B. pseudomallei (orf11)-the OIE recommended targets-resulted in negative signals. However, the presence of B. mallei in these tissues was conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Thorough genotype characterization of B. mallei strains would not only help to elucidate the origin of Pakistani strains, but also the detection and surveillance of glanders worldwide. Laroucau et al [36] reported that in two horses that were serologically tested and found to be positive for glanders, the routine PCR with tissue targeting the fliP-IS407A gene did not give a positive result, probably due to genetic variation in the infecting strains. Solely by applying more extensive methods, like SNP and MLST typing, the serological results could be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Thorough genotype characterization of B. mallei strains would not only help to elucidate the origin of Pakistani strains, but also the detection and surveillance of glanders worldwide. Laroucau et al [36] reported that in two horses that were serologically tested and found to be positive for glanders, the routine PCR with tissue targeting the fliP-IS407A gene did not give a positive result, probably due to genetic variation in the infecting strains. Solely by applying more extensive methods, like SNP and MLST typing, the serological results could be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia mallei is a small rod-shaped, Gram-negative bacterium that causes glanders, a notifiable disease in animals and humans [ 1 ]. Glanders is extremely contagious among Equidae , especially for horses and donkeys [ 2 , 3 ]. In many cases, infected animals need to be euthanized following governmental regulations on the eradication of epizootic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The cELISA was further evaluated with horse sera from glanders outbreaks in Bahrain [ 9 – 10 ] and Kuwait [ 11 ]. The outbreak in Bahrain was a result from horses imported from Syria via Kuwait.…”
Section: Discussionmentioning
confidence: 99%
“…The 31 seropositive sera were obtained from two separate glanders outbreaks in the Middle East. These included 25 horse sera from a glanders outbreak in Bahrain in year 2010–2011 [ 9 – 10 ] and 6 horse sera from a glanders outbreak in Kuwait in year 2019 [ 11 ]. All serum samples were confirmed as seronegative or seropositive for glanders using the complement fixation test (CFT), which served as the gold standard in this study [ 12 ].…”
Section: Methodsmentioning
confidence: 99%